2017
DOI: 10.1016/j.engfracmech.2017.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of ductile fracture in single point incremental forming using a modified GTN model

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. t r a c tUnderstanding the deformation and failure mechanisms in single point incremental forming (SPIF) is of great importance for achieving improved formability. Furthermore, there wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…Extensive research has been carried out to explain the deformation and fracture mechanism in ISF through theoretical analysis and experimental testing [22][23][24][25][26][27][28][29]. The results of these studies showed that the deformation and fracture in ISF part occur due to different mechanisms i.e.…”
Section: Modelling Of Ductile Fracture In Isfmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research has been carried out to explain the deformation and fracture mechanism in ISF through theoretical analysis and experimental testing [22][23][24][25][26][27][28][29]. The results of these studies showed that the deformation and fracture in ISF part occur due to different mechanisms i.e.…”
Section: Modelling Of Ductile Fracture In Isfmentioning
confidence: 99%
“…q 1 ; q 2 and q 3 ¼ q 2 1 . A detailed description of modified GTN model can be found in [24,32]. A brief overview of the constitutive equation of GTN damage model is provided in this section In order to maintain consistency.…”
Section: Modelling Of Ductile Fracture In Isfmentioning
confidence: 99%
“…In this area, FEA helps to gain in-depth understanding of the strain and stress development as well as the fracture. On the other hand, many damage models have been developed based on classic fracture theories, including Gurson-Tvergaard-Needleman model and Lemaitre continuum damage mechanics model to provide an insight in fracture mechanisms [61][62][63][64]. Similar studies are making progress in the DSIF field based on the methods such as FEA [7], parametric research [28,29], or the stress analysis amended from the previous SPIF studies [30].…”
Section: Deformation Mechanisms Of Disfmentioning
confidence: 99%
“…14, the maximum damage occurred in the transition zone between the contact area and formed wall rather than the contact area itself. Gatea et al [75] also adopted the GTN model with the Nahshon-Hutchinson shear mechanism to predict the fracture when deforming pure titanium. In their simulations, the GTN model with shear mechanism predicted earlier occurrence of fracture; however, more accurate results were predicted in both the conic shape and the pyramid shape than that by the original GTN model, which suggested a clear influence of shear deformation in the SPIF process.…”
Section: Prediction Of Fracture Initiation By Fe Damage Modelingmentioning
confidence: 99%
“…16 Schematic representation of a cross-sectional view of the SPIF process [78] Stretching effect Fig. 15 Numerical results of the porosity for the shear modified GTN model upon fracture [75] However, the width of the groove was almost equal to the diameter of the tool; the features of ISF deformation were not fully represented by the groove test. The relative dimension of the tool to the part was far too large compared to that in the actual ISF experiment, thus creating a distinctive contact conditions therefore a different stress/strain distribution.…”
Section: Suppression Of Necking In Spifmentioning
confidence: 99%